ANTIBACTERIAL ACTIVITY OF METHYLGLYOXAL AGAINST MULTI-DRUG RESISTANT SALMONELLA TYPHI: Multi-Drug Resistant Salmonella Typhi - Afzal, Dr Raja Kamran; Hannan, Abdul; Ahmed, Syed Azhar; Khalid, Fizza (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the antibacterial activity of MGO against MDR Salmonella typhi isolated from blood culture specimens and compare this activity against non-MDR S. typhi and with other gram negative rods. Study Design: Experimental study. Place and Duration of Study: Department of Microbiology, University of Health Sciences Lahore, from Jul 2011 to Jun 2012. Material and Methods: A total of 157 isolates of S. typhi were collected from different hospitals of Lahore and kept stored at -80°C. Morphological, biochemical and serological identification and antibiotic susceptibility testing of the isolates was carried out as per CLSI 2011 guidelines. Agar dilution method was used for the determination of MICs of MGO, using a multi-point inoculator. The data was compiled and results were determined using SPSS version 17. Results: Ninety-seven out of 157 isolates (61.8%) were MDR S. Typhi, while 60 (38.2%) were non-MDR S. Typhi. MIC90 of MGO against MDR S. Typhi isolates was (0.20 mg/mL; 2.8 mM), against non-MDR S. Typhi and Gram negative rods each, it was (0.21 mg/mL; 3.0 mM). When MICs of MGO against MDR S. Typhi group were compared to those of non-MDR S. Typhi group, the p-value was 0.827 (p>0.05; statistically insignificant). Whereas, the p-value of MICs of MGO against MDR S. Typhi group was 0.023 (p<0.05; statistically significant) when compared to gram negative rods group. Conclusion: MGO has good antibacterial activity against MDR and non-MDR S. Typhi, and other genera of Gram negative rods.